STUDI KASUS: TERAPI ACUPRESSURE DALAM MENGATASI EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I - Azizatul Khakimah; Niken Grah Prihartanti; Kolifah Kolifah (Jurnal Kebidanan, 2022)
The increase of hormone HcG, progesterone, and estrogen in pregnancy period causes complaints of nausea called emesis gravidaruam. The case study results showed that 3 out of 10 pregnant women complain of nausea. If nausea occurs continuously until lose energy to carry out activities, it is possible that the pregnant woman has hyperemesis gravidarum. Appropriate treatment in reducing emesis gravidarum can be done non-pharmacologically by providing acupressure therapy which is carried out at the Pc 6, St 36, Lv 14, Ren 17 and Bl 21 meridians as well as counseling. Using the case study method by approaching midwifery care. The research subjects were 2 primigravida pregnant women with gestational age 6-12 weeks, nausea without interfering with activities, nausea, decreased appetite and weight loss <5% of previous body weight. This study showed that in patient 1 after 7 days of midwifery care there was a decrease in the frequency of nausea by giving acupressure, counseling and giving crackers or biscuits and an increase in appetite so that the body weight increased by 1 kg, this was supported by the number of snacks consumed. Patient 2 after 2 days of midwifery care showed that acupressure and counseling could reduce the frequency of nausea. Giving acupressure therapy can be carried out in midwifery care in first trimester pregnant women with emesis gravidarum.